Logarithmic to nonlogarithmic flux creep transition and magnetic flux hardening in BiSrCaCuO superconducting ceramics - Safar, H.; Durán, C.; Guimpel, J.; Civale, L.; Luzuriaga, J.; Rodríguez, E.; de la Cruz, F.; Fainstein, C.; Schneemeyer, L.F.; Waszczak, J.V.; Guimpel, Julio (Elsevier, 1989)
Fil: Safar, H. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina